Law Enforcement towards Online Mass Media Abuse According to the Press Law - Andiniya Komalla Parawita (Ius Poenale, 2021)
The resolution process of law enforcement related to press offences differs in Indonesia. The disparity in resolving legal issues arising from press violations in Indonesia is due, in part, to differing interpretations of press regulations. Some actions were taken under Law No. 40 of 1999 Concerning the Press (Press Law). Some issues were resolved through the Criminal Code or the Kitab Undang-Undang Hukum Pidana (KUHP). This study is interested in looking into law enforcement against the abuse of mass media through online media in terms of press law and the Criminal Code and the barriers to its enforcement. The method used in this research is a normative juridical and empirical juridical approach. Subsequently, data analysis uses qualitative analysis methods. The paper concludes by arguing that enforcing press law against abuse of mass media through online media is accomplished by enforcing Article 5 paragraph (1) of the Press Law. However, Article 5 paragraph (1) of the Press Law does not regulate or formulate the delusions of defamation and insults as regulated in Article 310 of the Criminal Code. The absence of norms and conditions for when and in what cases the press can and cannot be brought to court for violating criminal law and sentenced to criminal sanctions is a barrier in law enforcement on the misuse of mass media through online media associated with press laws.